Tasks Beyond Instruction: A Case Study on Teachers’ Ancillary Functions - Jophil Q. Arañas (International Journal of Educational Innovation and Research, 2023)
Teachers play multi-faceted roles. In addition to teaching, they also perform duties not directly related to teaching but are part of school’s operations. As one of the rural schools in the Division of Ozamiz City, Sangay Integrated School teaching personnel are tasked to take multiple ancillary functions. This study explored the experiences of teachers having ancillary functions in Sangay IS for the School Year 2022-2023. It employed a case study research design where twelve (12) Sangay Integrated School served as the participants of this study. It utilized a semi-structured interview, and the data gathered were analyzed using Braun and Clarke’s thematic analysis. It generated five (5) themes, which answered the five (5) research problems. Based on the findings, teachers regard ancillary functions as additional tasks. These functions help teachers in their personal and professional development; however, time for instruction and family is sacrificed. To overcome this challenge, they employed workload management. They realized they needed assistance from more knowledgeable individuals to function effectively and efficiently, which can be done through mentoring, seminars, and training. It is recommended that school leaders may evenly distribute ancillary loads. Teachers may also create a checklist to balance their time well on what things are needed to do. An orientation for newly-appointed coordinators may also be done for their awareness of their responsibilities. The Department of Education may also employ a thorough and accurate time-use study that can clearly show which tasks should be assigned to teachers and which should be removed from their responsibility.